The templars and their sources - Borchardt, Karl; Döring, Karoline Dominika; Josserand, Philippe; Nicholson, Helen J. (Crusades / Subsidia, 2017)
Section I. Headquarters -- Vestiges of Templar presence in the Aqsa Mosque / Benjamin Z. Kedar -- The Templars and the kings of Jerusalem / Jochen Burgtorf -- The Templars' archives in Syria and Cyprus / Anthony Luttrell -- Section II. Charters -- Templar charters and charters for the Templars: self-promotion versus the image of the order / Karl Borchardt -- Copies and cartularies: modernizing Templar documents in mid-thirteenth century Champagne / Michael J. Peixoto -- Private charters and other family documents in the Templar archives: commanderies in southern France / Damien Carraz -- Editing Templar charters in the Iberian Peninsula at the beginning of the twenty-first century / Philippe Josserand -- The Marquis of Albon, Carl Erdmann and the Templar sources in Portugal / Kristjan Toomaspoeg -- Section III. Constitution, structure and finance -- The office of master deça mer in military orders / Alan Forey -- Die prokuratoren der templer: diplomatische und rechtliche aspekte ihrer einsetzung und ihrer Aufgaben: English summary / Christian Vogel -- Templar tactics: the order on the battlefield / John France -- Les ordres religieux-militaires et l'argent: sources et pratiques: English summary / Alain Demurger -- Section IV. Spiritual character -- Les templiers et le progressif évanouissement de leur règle: English summary / Simonetta Cerrini -- The documentary evidence for Templar religion / Jochen Schenk -- Gab es eine spiritualität der templer: English summary / Arno Mentzel-Reuters